Study of Medicinal Plants for Traditional Malaria Treatment - Innal Saitis; Ferdinta Daniasta Setyawan; Fenska Narly Makualaina (GLOBAL HEALTH SCIENCE GROUP, 2026)
The pharmaceutical world is also revisiting traditional medicine. The use of plants or natural ingredients as medicine is known as traditional medicine. Traditional medicine, or herbal medicine, refers to ingredients or concoctions derived from plants, animals, minerals, or a combination of these ingredients. This poses a challenge in efforts to prevent and control malaria in Jayapura. The objective of this study is to examine medicinal plants used in traditional malaria treatment in the Harapan Community Health Center Working Area. This study is a qualitative study with a phenomenological approach. The techniques used are in-depth interviews and observation. The informants selected are those who have had malaria, malaria sufferers, and families of sufferers. a total of 41 respondents with malaria. In this study on the use of traditional medicine for malaria treatment, the sample size was originally planned to be 100 respondents, but only 41 malaria respondents were obtained. This was due to the limited time frame of the study, which ended in July 2025. All respondents were malaria patients who visited the health center, as well as long-term patients who were visited directly at their homes in order to meet the required sample size. The types of medicinal plants used by the community in the Harapan Community Health Center working area are papaya, yellow string.